Characteristics of soybean (Glycine max) protein hydrolysate by bromelain and its effect on inflammation and kidney disorders in gentamicin-induced male Wistar rats - Meilinah Hidayat; Amirah Barnas; Virginia Nussy; Timothy Wantania; Sriwidodo Sriwidodo; Khomaini Hasan (Iranian Journal of Basic Medical Sciences, 2025)
Objective(s): Soybeans have various positive effects on health, including anti-inflammatory and preventing kidney damage. There is concern regarding the phytoestrogen content due to the high isoflavone content in soybeans. Various forms of soybean processing have been tried; in this study, the hydrolysis method will be used to obtain the active substance Arginine-Glycine-Aspartate (RGD) tripeptide in soybean protein hydrolyzed by bromelain (SPHB). The research aimed to determine the characteristics and influence of SPHB on kidney function, inflammation, body weight, and estrogen in male Wistar rats induced by gentamicin.Materials and Methods: Soybeans (Glycine max) are hydrolyzed using the proteolytic enzyme Bromelain from pineapples. The proteomics was investigated using Liquid-Chromatography Mass Spectroscopy Tandem (LC-MS/MS). SPHB in three doses would be tested for 28 days on male Wistar rats induced by gentamicin. The parameters measured were body weight, high-sensitive cell reactive protein (hs-CRP) levels, urea, creatinine, and estrogen levels.Results: SPHB has a low molecular weight (LMW) of 10 kDa and contains RGD in the lunasin sequence. SPHB showed no effect on body weight (P>0.05). The impact of SPHB on hs-CRP, urea, and creatinine showed differences significantly from the positive control, especially SPHB at a dose of 112 mg/day (P<0.01). Meanwhile, SPHB has almost no effect on estrogen levels.Conclusion: The administration of SPHB with LMW and contains lunasin showed decreased inflammation and kidney function parameters but did not affect body weight and estrogen levels in induced gentamicin Wistar rats.